2019
DOI: 10.3892/etm.2019.8295
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR‑34a in cataract rats and its related mechanism

Abstract: Expression of miR-34a in cataract rats and its related mechanism were investigated. A total of 30 SD rats were selected and divided into three groups: group A: 2-month-old lucent lens, group B: 18-month-old lucent lens, and group C: 18-month-old naturally occurring cataract lens. The lens was taken and measured by LOC III to determine the degree of lens opacity of the three groups of rats. qPCR was used to detect expression of miR-34a and mRNA of SIRT1 and P53. Western blotting was used to detect the protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As an miRNA member, prior studies have indicated that miR-34a is deregulated in various cancers ( Li et al ., 2019 ; Liu et al ., 2020 ; Xiu et al ., 2020 ). Besides, it is the first miRNA found to be directly regulated by p53 ( Rokavec et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an miRNA member, prior studies have indicated that miR-34a is deregulated in various cancers ( Li et al ., 2019 ; Liu et al ., 2020 ; Xiu et al ., 2020 ). Besides, it is the first miRNA found to be directly regulated by p53 ( Rokavec et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…They may exist in a stable state within cells or outside cells in biological fluids, including plasma and aqueous humor (AH), vitreous humor, serum, saliva, urine, and tears, and can exist as exosomes or be bound to carrier proteins [20,21]. Previous studies have reported that the expression of miRNAs can be involved in senescence or age-related neurological disorders, diabetes, degenerative arthritis, carcinomas, and cataracts [16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In glaucoma, miRNAs can regulate ECM metabolism by regulating TGF-β and can regulate stiffness by the accelerated maturation of ECM proteins, altering the trabecular meshwork (TM) contractile properties, thus accelerating or inhibiting TM cell senescence, or by modulating oxidative-and mechanical-stress-induced damage [20,22,38] in the cell/tissue(Table 1).…”
Section: Potential Role Of Mirnas In Xfgmentioning
confidence: 99%
“…Moreover, it inhibits cell death following DNA injury by antagonizing p53 acetylation (27). The upregulation of miRNA-34a expression level is associated with cataract occurrence in rats, which may be caused by down-regulation of Sirt1 protein (28). Sirt1 protects LECs from oxidative stress by inhibiting the p53 pathway (29).…”
Section: Introductionmentioning
confidence: 99%